2019
DOI: 10.5582/bst.2019.01173
|View full text |Cite
|
Sign up to set email alerts
|

The community-based integrated care system in Japan: Health care and nursing care challenges posed by super-aged society

Abstract: An elderly population refers to the proportion of persons age 65 years or older out of the total population. The World Health Organization (WHO) and the United Nations define an "aging society" as one in which more than 7% of the population is 65 years or older, an "aged society" as a society in which more than 14% of the population is 65 years or older, and a "super-aged society" as a society in which more than 21% of the population is 65 years or older (1,2). Japan is experiencing population aging that is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 3 publications
0
51
0
5
Order By: Relevance
“…Based on the above results, further research is needed to reveal how host societies can enrich opportunities for immigrants' mental health and improve access to social networks for support. There is an international movement toward developing a community-based integrated mental health service, in which mental health professionals and policy makers work together [57][58][59]. Recent review articles have suggested that an integrated care system for young people was effective for the prevention of mental illness and for early intervention [42].…”
Section: Community-based Integrated Care System and Implementationmentioning
confidence: 99%
“…Based on the above results, further research is needed to reveal how host societies can enrich opportunities for immigrants' mental health and improve access to social networks for support. There is an international movement toward developing a community-based integrated mental health service, in which mental health professionals and policy makers work together [57][58][59]. Recent review articles have suggested that an integrated care system for young people was effective for the prevention of mental illness and for early intervention [42].…”
Section: Community-based Integrated Care System and Implementationmentioning
confidence: 99%
“…Community-based integrated care system and implementation Based on the above results, further research is needed to reveal how host societies can enrich opportunities for immigrants' mental health and improve access to social networks for support. There is an international movement toward developing a community-based integrated mental health service, in which mental health professionals and policy makers work together [57][58][59]. Recent review articles have suggested that an integrated care system for young people was effective for the prevention of mental illness and for early intervention [42].…”
Section: Limitationsmentioning
confidence: 99%
“…Community-based integrated care system and implementation Based on the above results, further research is needed to reveal how host societies can enrich opportunities for immigrants' mental health and improve access to social networks for support. There is an international movement toward developing a community-based integrated mental health service, in which mental health professionals and policy makers work together [56][57][58]. Recent review articles have suggested that an integrated care system for young people was effective for the prevention of mental illness and for early intervention [42].…”
Section: Limitationsmentioning
confidence: 99%